The relationship between body image and nutritional behaviors in adult individuals - Merve Pehlivan; Neslişah Denkçi; Reyhan Pehlivan; Muhammet Ali Çakır; Yeliz Mercan (PLoS ONE, 2025)
Objective Dissatisfaction with body image and maladaptive nutritional behaviors can have profound effects on psychological, social, and physical health and may pave the way for the development of eating disorders. However, research into this topic in the adult population is relatively limited. Therefore, this study aimed to examine various factors affecting dissatisfaction with body image and maladaptive nutritional behaviors in adults living in Türkiye and the relationship between these two concepts. Methods This descriptive study was conducted with 3,153 adult individuals who were ≥  18 years old living in Türkiye. The data of the study, which was conducted as an online survey, were collected using the Descriptive Information Form, the Body Image Scale, and the Three-Factor Eating Questionnaire. Results Of the participants, 70.1% were women. The mean age was 28.02 ± 9.27 (Min.: 18, Max.: 74) years. The relationship between the mean scores on the total Body Image Scale and Uncontrolled Eating (r = -0.094, p < 0.000), Emotional Eating (r = -0.171, p < 0.001), and Susceptibility to Hunger (r = -0.108, p < 0.001) scores was negative. A statistically significant and positive relationship was detected between the mean scores on the total Body Image Scale and the Cognitive Restraint score (r = 0.089, p < 0.001). Statistically significant relationships were detected in the model adjusted for age and gender between the Body Image Scale and Emotional Eating scores (B = -1.085, p < 0.000), and Cognitive Restraint scores indicated positive relationships (B = 0.848, p < 0.001). Conclusion Body image satisfaction was found to be negatively associated with uncontrolled eating, emotional eating, and susceptibility to hunger. On the other hand, a positive relationship was found between body image satisfaction and cognitive restraint. These findings highlight the critical importance of body image satisfaction on eating behaviors and provide potential insight into prevention and intervention programs to improve body image to promote adaptive eating behaviors in the adult population.